The cytokine gene polymorphisms (TNF-α, IL-10 And IFN-γ) and the role of inflammatory cytokines in diabetic neuropathy - Ramesh, M.; Kumari, Konathala Geetha; Sudhakar, G. (International Journal of Research in Medical Sciences, 2017)
Background: One of the most frequently-occurring micro vascular complications is diabetic neuropathy (DN). Diabetic nephropathy (DN) affects approximately one third of people with type 1 or type 2 diabetes mellitus The objective of the study is an attempt to examine functional SNPs primarily at the position on gene of TNF-α (-308 G/A, rs 1800629), IL-10 (-1082 G/A, rs 1800896) and IFNγ (+874 A/T, rs 62559044) in order to establish their association with peripheral neuropathy patients with type 2 diabetes. Methods: 150 cases presenting Diabetic neuropathy and 160 cases of age and sex matched healthy controls were included in the study. ARMS PCR was done for genotyping of TNF-α (-308), IL-10 (1082 G/A) and IFNγ (+874) polymorphism using allele specific primers for detection of single nucleotide polymorphisms. Analysis of the data was carried out using Epi Info 5 software. In addition, the gene frequencies were estimated and goodness of fit between the observed and expected phenotype frequencies was tested. Multifactor Dimensionality Reduction (MDR) analysis was performed to study case-control data and gene-gene interactions. Results: The results revealed that the chi- square test for heterogeneity for IL-10 system was found to be significant (χ² = 16.2380; d.f = 2; p >0.001) between patients and controls, indicating a significant departure from the HWE. Thus, the test of association of both homogeneity and heterogeneity of IL-10 showed a significant difference, indicating an association of IL-10 with diabetic neuropathy.SNPs at position −308 promoter gene of TNF-α and IFNγ (+874) were not significantly associated with development of Diabetic Neuropathy. Conclusion: This case-control study suggests that IL-10-1082G/G polymorphism is associated with the susceptibility to diabetic neuropathy in type 2 DM patients. IL-10 serves as an important bio marker in Indian population for their susceptibility to Diabetic Neuropathy as it may play a role in alteration of IL-10 production and the inflammatory responses.